THE POETIC ISSUES IN XURSHID ABDURASHID’S POETRY (European Journal of Interdisciplinary Research and Development, 2024)
Xurshid Abdurashid is one of the prominent figures of contemporary Uzbek literature, whose works reflect poetic style, artistic imagery, and profound philosophical meanings. His poetry masterfully conveys human emotions, natural landscapes, and national values through unique poetic expression.